Anatomy of trisomy 18. Issue 5 (3rd May 2016) - Roberts, Wallisa; Zurada, Anna; Zurada‐ZieliŃSka, Agnieszka; Gielecki, Jerzy; Loukas, Marios
Abstract : Trisomy 18 is the second most common aneuploidy after trisomy 21. Due to its multi‐systemic defects, it has a poor prognosis with a 50% chance of survival beyond one week and a <10% chance of survival beyond one year of life. However, this prognosis has been challenged by the introduction of aggressive interventional therapies for patients born with trisomy 18. As a result, a review of the anatomy associated with this defect is imperative. While any of the systems can be affected by trisomy 18, the following areas are the most likely to be affected: craniofacial, musculoskeletal system, cardiac system, abdominal, and nervous system. More specifically, the following features are considered characteristic of trisomy 18: low‐set ears, rocker bottom feet, clenched fists, and ventricular septal defect. Of particular interest is the associated cardiac defect, as surgical repairs of these defects have shown an improved survivability. In this article, the anatomical defects associated with each system are reviewed. Clin. Anat. 29:628–632, 2016. © 2016 Wiley Periodicals, Inc.